USP20 mediates malignant phenotypic changes in bladder cancer through direct interactions with YAP1 - Wensun Chen; Siqi Wu; Yifan Chen; Weijian Li; Yiqing Cao; Yingchun Liang; Xiyu Dai; Xinan Chen; Yilin Chen; Tian Chen; Shenghua Liu; Chen Yang; et al. (Neoplasia: An International Journal for Oncology Research)
Yes-associated protein 1 (YAP1) has attracted attention for its potential in the treatment of various types of malignancies. The Hippo-YAP1 axis is inhibited in bladder cancer (BC), which is a major driver of BC progression and oncogenesis. Hippo pathway activity is controlled by the phosphorylation cascade in the MST1/2-LATS1/2-YAP1 axis, in addition to other modifications such as ubiquitination of the Hippo pathway proteins through the co-regulation of E3 ligases and deubiquitinases. In this study, we identified USP20 as a Hippo/YAP1 pathway-related deubiquitinase using combined siRNA screening and a deubiquitinase overexpression assay. Further analysis revealed that USP20 directly regulated the expression of YAP1 and its downstream target genes connective tissue growth factor and cysteine-rich angiogenic inducer 61. A tissue microarray assay confirmed that USP20 expression was elevated in tumor tissues and correlated with YAP1 expression. Analysis of the underlying mechanisms revealed that USP20 directly interacted with the YAP1 protein and promoted its stability through inhibition of K48-linked poly-ubiquitination. Our findings revealed that USP20 serves as a deubiquitinase and regulates the Hippo-YAP1 pathway in BC.